Dogma and ecumenism Vatican II and Karl Barth's Ad Limina Apostolorum - Levering, Matthew 1971-; McCormack, Bruce L. 1952-; White, Thomas Joseph 1971- (<<The>> Catholic University of America Press, 2020)
"Catholic and Protestant theologians reflect upon the five major documents of Vatican II through the lens of Karl Barth's response to the council"--
Includes bibliographical references and index
Keywords: Barth, Karl -- 1886-1968 -- Ad limina apostolorum; Vatikanisches Konzil -- 2. -- 1962-1965 -- Vatikanstadt -- Ad gentes; Ökumenische Theologie; Barth, Karl / 1886-1968 / Ad limina apostolorum; Catholic Church / Doctrines; Catholic Church / Relations / Protestant churches; Vatican Council / (2nd / 1962-1965 / Basilica di San Pietro in Vaticano); Protestant churches / Doctrines; Protestant churches / Relations / Catholic Church; Aufsatzsammlung; Konferenzschrift -- 2016 -- Washington, D.C.